2019
DOI: 10.1038/s41589-019-0242-5
|View full text |Cite
|
Sign up to set email alerts
|

Addendum: A cellular chemical probe targeting the chromodomains of Polycomb repressive complex 1

Abstract: In the version of this article originally published, several lines of text in the last paragraph of the right column on page 1 of the PDF were transposed into the bottom paragraph of the left column. The affected text of the left column should read "The ATP-dependent activities of the BAF (SWI/SNF) chromatin remodeling complexes affect the positioning of nucleosomes on DNA and thereby many cellular processes related to chromatin structure, including transcription, DNA repair and decatenation of chromosomes dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The availability of a negative control is important to enable cellular and in vivo studies to be carried out with a matched pair of compounds that are as similar as possible in their structure, physical properties, and off-target profiles, while differing greatly in their on-target activity. Based on prior SAR, which showed that epimers at the leucine position did not bind to CBX CDs ( Stuckey et al, 2019 ), we substituted L-cyclobutyl glycine for D-cyclobutyl glycine resulting in compound 35 ( Figure 5A , bottom). As expected, compound 35 displayed a negligible effect on de-repression of GFP in the CBX8 reporter assay ( Figure 5B ).…”
Section: Resultsmentioning
confidence: 99%
“…The availability of a negative control is important to enable cellular and in vivo studies to be carried out with a matched pair of compounds that are as similar as possible in their structure, physical properties, and off-target profiles, while differing greatly in their on-target activity. Based on prior SAR, which showed that epimers at the leucine position did not bind to CBX CDs ( Stuckey et al, 2019 ), we substituted L-cyclobutyl glycine for D-cyclobutyl glycine resulting in compound 35 ( Figure 5A , bottom). As expected, compound 35 displayed a negligible effect on de-repression of GFP in the CBX8 reporter assay ( Figure 5B ).…”
Section: Resultsmentioning
confidence: 99%
“…Our search for a negative control for UNC7040 illustrates some of the challenges in creation of the ideal negative control that are perhaps not widely appreciated. Based on prior SAR, that showed that epimers at the leucine position did not bind to CBX CDs (Stuckey et al, 2019), we substituted L-cyclobutyl glycine for D-cyclobutyl glycine resulting in compound 35 ( Figure 5A , bottom). As expected, compound 35 displayed a negligible effect on de-repression of GFP in the CBX8 reporter assay ( Figure 5B ).…”
Section: Resultsmentioning
confidence: 99%
“…The purpose of these molecules is to inhibit the reader function of the CBX protein or to dissociate the PRC1 complex. UNC3866 [30] is a recently reported peptidyl chemical probe for PRC1.It can effectively inhibit the proliferation of PC3 cells by selectively binding to CBX7 [31] . It is recommended that more speci c PRC inhibitors can be developed in the future.…”
Section: Discussionmentioning
confidence: 99%